Studi Kelayakan Pendirian Program Studi Profesi Apoteker di Universitas Mataram, Nusa Tenggara Barat - Agriana Rosmalina Hidayati; Candra Eka Puspitasari; Anggit L. Sunarwidhi; Siti Rahmatul Aini; Iman Surya Pratama Pratama; Baiq Ihda Nanda Safriyana (Universitas Mataram, 2022)
West Nusa Tenggara (NTB) is one of the provinces that does not yet have educational facilities for the Pharmacist Professional Study Program, although it already has several Bachelor of Pharmacy Study Programs, one of which is at the University of Mataram. The pharmacist profession program aims to produce pharmacists who are expected to improve health services in West Nusa Tenggara. However, establishing a study program requires a feasibility analysis of the establishment. This feasibility study research is descriptive in nature using a qualitative design with a case study method, namely by taking pictures and describing an overview of the Pharmacist Professional Study Program feasibility study, Faculty of Medicine, University of Mataram. The instrument for collecting qualitative research data is the researcher as the main instrument equipped with a guide for observations, interviews, and document searches summarized in a Forum Group Discussion (FGD) activity. The results obtained the formation of the curriculum, the establishment of tuition fee, the preparation of a strategic plan which is the result of the process of preparing the management, the arrangement of human resource development methods, and the establishment of a special education facility as well as a computer-based exam room (CBT) and Objective Structured Clinical Examination (OSCE). We can be concluded that the PSPA Mataram University deserves to be established